Seasonal and continual wind speed modelling for the coastal urban city, Karachi - SADIQ, NAEEM (MAUSAM, 2018)
ABSTRACT. Variation in wind speed not only indicates the strengthening or weakening of pressure systems but its role in wind farm in the vicinity of coastal area is also crucial. Probability distributions through time series of wind speed data serves foremost basic need for the said parameters. Exploratory data analysis revealed that for coastal city Karachi, maximum wind speed ( 23 m/s) occurred during monsoon with its peak during postmonsoon with maximum deviation ( 3.5 m/s). Mean / trimmed mean during spring and postmonsoon ( 11.5 m/s) as well as in premonsoon and monsoon ( 18.5 m/s) remain almost identical while minimum wind blowing during winter and postmonsoon are also identical ( 6 m/s). Autumn and winter exhibits least standard deviations. Critical and statistical values have been compared for distribution modelling, while parametric values of different seasonal and continual distributions are also estimated. The study is supported by cumulative distribution functions and probability-probability plots. It is not uncommon to use Weibull distribution for wind speed modelling. By using daily data time series of wind speed for the coastal station Karachi, it has been explored that widely accepted Weibull distribution provides comparatively poor distribution results when compared to other more complicated models (i.e., Wakeby and generalized extreme value distributions]. It is found that annual and seasonal wind comes after the Wakeby distribution except premonsoon summer which follows the generalized extreme value distribution (GEV) for the city. No continual and / or seasonal wind speed follows the Weibull distribution, ultimately and / or more appropriately. The study may give some new insights for aviation and wind engineering purposes.